Sociodemographic factors that determine the entrepreneurship in the northern macro-region of Peru - Condor Correa, Ranjky (2024)
The objective of the study was to determine the personal sociodemographic factors that determine the entrepreneurship of one's own businesses in the northern macro-region of Peru. Methodologically, it was a quantitative, basic, explanatory study, with a non-experimental design. Likewise, the sampling capacity was made up of 30,183 and 30,673 private homes, respectively, with 20,265 and 20,595 homes corresponding to the urban area and 9,918 and 10,078 homes to the rural area in both 2021 and 2022. Using documentary analysis of secondary source data, worked under a model probit. The results showed that when the participant does not play the role of head of household, they have the 0.79% entrepreneurship capacity, compared to those who are heads of household, who have a higher rate of entrepreneurship of 2.42%. Likewise, it is highlighted that the lack of employment has not proven to be a factor for starting a business in 95.95%, finding a significant link between entrepreneurship and the rest analyzed factors (p<0.05). In conclusion, entrepreneurship is affected by a variety of sociodemographic aspects; likewise, current employment is not considered a decisive factor, unlike the other factors that do play a determining role.